Supplementation of Crab (Portunus pelagicus) Shell Calcium Flour on Commercial Feed on Freshwater Lobster (Cherax quadricarinatus) Molting Frequency - Azizah Mahary; Andri Pratama Wibowo (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Freshwater lobster (Cherax quadricarinatus) is a type of crustacean (crustacean). Freshwater lobster is a type of shrimp that lives in shallow fresh inland waters, with a muddy substrate and lots of gaps and cavities to hide. The cultivation of freshwater lobsters is quite easy because the tolerance to the environment is quite high with relatively few disease problems. Molting is a natural process that occurs in freshwater lobsters as their bodies grow. Calcium is one of the mineral elements that lobsters really need to form new shells. In addition to calcium, lobsters will also undergo a mineralization process to form new membranes using calcium absorbed from the environment in which they live. The purpose of this study was to determine the effect of supplementation of calcium flour from crab shells on commercial feed on molting frequency, absolute weight and length, survival of freshwater lobster, and determine the appropriate dose of calcium flour supplementation of crab shells. This study used a completely randomized design (CRD) with 4 treatments and 4 replications with additional doses of calcium flour, 0%, 2%, 4%, and 6% per kg of feed. The stock density of freshwater lobster was 7 individuals per aquarium for 30 days of rearing. The results showed that the addition of shell calcium powder of as much as 4% (treatment C) was the best dose with 2 molts/ind and the lowest was in treatment A (control). The highest growth in absolute weight and absolute length was at a concentration of 4% (treatment C) 2.34g and 1.55 cm, the lowest value was obtained at treatment A (control) 1.63g and 0.95 cm. Supplementation of crab shell calcium flour in commercial feed for crayfish did not have a significant effect on the survival (SR) of freshwater lobster